2020
DOI: 10.1071/py19183
|View full text |Cite
|
Sign up to set email alerts
|

Preventative and early intervention diabetes-related foot care practices in primary care

Abstract: The aim of this study was to identify current preventative and early intervention diabetes-related foot care practices among Australian primary care healthcare professionals. A survey was developed to obtain information about preventative and early intervention foot care actions, priorities of care, access and referral to expert multidisciplinary foot care teams and adherence to best-practice diabetes-related foot care recommendations. The survey was distributed to GPs and Credentialled Diabetes Educators (CDE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
6
0
2
Order By: Relevance
“…Fortunately, within Australia, a strong system of universal healthcare provides early access to medical treatment, subsidised medications and affordable referral to allied health professionals. However, even amongst healthcare professionals with extensive experience in diabetes care, delivery of best practice diabetes‐related footcare in primary care is inconsistent (Mullan et al., 2020). Barriers to footcare have been identified to be multifaceted, including geographical, administrative and communication limitations, referral and care guideline unavailability and implementation challenges, and limited human, service, equipment and funding resources (Mullan et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, within Australia, a strong system of universal healthcare provides early access to medical treatment, subsidised medications and affordable referral to allied health professionals. However, even amongst healthcare professionals with extensive experience in diabetes care, delivery of best practice diabetes‐related footcare in primary care is inconsistent (Mullan et al., 2020). Barriers to footcare have been identified to be multifaceted, including geographical, administrative and communication limitations, referral and care guideline unavailability and implementation challenges, and limited human, service, equipment and funding resources (Mullan et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Varying rates of foot screening have been reported in primary care (Davies, 2014). A study of 94 primary care clinicians found that just 45% of participants remove the shoes and socks of their patients with diabetes at a consultation (Mullan et al., 2020). Another study involving 46 primary care nurses identified that 100% had not received education on diabetes‐related foot assessments in their nursing training and 80% were not confident in conducting such assessments (Lakha & Lee, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported risk factors associated with reulceration including s poor glycemic control, 20 peripheral neuropathy, lower extremity artery disease, late foot ulcer diagnosis, non-adherence to appropriate footwear, and improper foot care. 16,17 In our study, the re-ulceration group had a long time of having diabetes as well as high failure rate in controlling HbA1c, so there could be more chronic complications (higher rate of monofilament loss of sensation and vascular stenosis) than in the non-re-ulcerative group. However, the duration of diabetes in foot ulcer patients in our study was shorter than in European and American studies.…”
mentioning
confidence: 68%
“…T2DPs admitted late and receiving treatment at provincial hospitals may still be at risk of poor treatment outcomes due to primary care practitioners not adhering to best practice foot care recommendations. 16 T2DPs initially sought care from a variety of different venues—primary care doctors, podiatrists, specialists, emergency rooms, and urgent care clinics—as determined by how serious their DFU and insurance status and access issues. 17 Strategies to improve early detection and treatment of diabetic foot ulceration include patient education, regular foot exams, and multidisciplinary care teams.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on offloading reported no benefit from silicone gel sheeting to prevent ulcer recurrence 94 , and significant differences in plantar pressures between a specialised shoe compared to canvas or participants' own shoes 52 . One study found only 45% of health professionals reported removing shoes and socks of their patients for foot assessment 95 , and two protocols were registered on preventive interventions 96,97 .…”
Section: Australian Studiesmentioning
confidence: 99%